PERKEMBANGAN AKUNTANSI GOODWILL DARI DIVERSIFIKASI MENUJU KESERAGAMAN - Trisna Dwiyanti Kadek (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
This paper aims to review the prior research related to change in accounting treatment for goodwill from diversification to uniformity. Literature review is used to organize this paper. The paper discusses and compares the former accounting treatment used by countries around the world and the new IFRS treatment for goodwill. The paper highlights that the new standard has significantly changed the treatment for goodwill. According to IFRS 3, goodwill acquired through a business combination is no longer amortized but tested for impairment. Despite this standard has created a uniformed goodwill accounting; however, there are still lots of debates due to considerable ambiguity and subjectivity which inherent in impairment test. Findings suggest that future paper should examine how financial statement preparers and auditor are dealing with this new goodwill accounting treatment.